Rethinking Adoption and Diffusion as a Collective Social Process: Towards an Interactional Perspective - Leeuwis, Cees; Aarts, N. (Springer, 2021)
Agricultural development is looked at as a process in which the adoption of innovations plays an important role. In this context, there has been considerable interest in understanding how adoption processes work. This chapter starts from the observation that adoption has been conceptualised in most research and development efforts as a process at the level of individuals and/or individual households, resulting in the dominance of social-psychological modes of thinking. Drawing on case experiences and recent theories of innovation, this paper points towards the critical role that several types of interdependencies play in adoption processes, which leads to the conclusion that in many instances, adoption must be regarded as a collective rather than an individual process. It is therefore important to complement and re-orient our thinking about adoption and resort to more sociological and interactional concepts and explanations. After a discussion of relevant concepts, the chapter concludes with some reflection on how this perspective may inspire a different way of approaching two topical issues in the realm of agricultural innovation: scaling and ICT4Ag.